1968
DOI: 10.1071/ar9681029
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the number of ewes joined per ram for flock matings under paddock conditions. I. Mating behaviour and fertility

Abstract: In a series of six experiments rams were joined either singularly or in groups to varying numbers of ewes so that the number of ewes joined per ram varied between 25 and 100. Under the conditions of these experiments, decreasing the number of ewes joined per ram was associated with more rams serving each oestrous ewe, a greater proportion of ewes served during the first 2 weeks of joining, less ewes remaining unserved at the end of a 6 week joining period, and higher fertility (the proportions of ewes lambing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…These data are in agreement with Allison (1975) and other New Zealand reports (Haughey 1959;Edgar 1965), but contrary to reports with Merino sheep in which increasing the number of ewes per ram has usually resulted in a lower proportion of ewes mated during the first 2 weeks of mating, more ewes remaining unmated, fewer rams mating each oestrous ewe, and a lower percentage of ewes lambing (Lightfoot & Smith 1968;Croker 1970;Dawe et at. 1974).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These data are in agreement with Allison (1975) and other New Zealand reports (Haughey 1959;Edgar 1965), but contrary to reports with Merino sheep in which increasing the number of ewes per ram has usually resulted in a lower proportion of ewes mated during the first 2 weeks of mating, more ewes remaining unmated, fewer rams mating each oestrous ewe, and a lower percentage of ewes lambing (Lightfoot & Smith 1968;Croker 1970;Dawe et at. 1974).…”
Section: Discussionsupporting
confidence: 80%
“…1971(Mattner et at. , 1973 and semen quality (Lightfoot 1968), which result in a reduction in the number of ewes mated (Croker & Lindsay 1972) and in ewe fertility, particularly at higher numbers of ewes per ram (Lightfoot & Smith 1968;Croker 1970). Also Dobbie (1974) has recorded low fertility in some flocks mated with a low percentage of 1 1/z-year-old rams in New Zealand, supporting Haughey's (1959) suggestion that "shearling" rams were of lower fertility than older rams.…”
Section: Discussionmentioning
confidence: 98%
“…Australian work with Merinos has shown that two-tooth rams mate with fewer ewes and sometimes are not as fertile as older rams (Lightfoot & Smith 1968;Croker 1970;Croker & Lindsay 1972;Mattner et al 1971Mattner et al , 1973. Two ram age groups joined with different numbers of ewes per ram were compared in two experiments to provide information on the Romney breed.…”
Section: Introductionmentioning
confidence: 99%
“…Lightfoot and Smith (1968) found a ratio of 25 : 1 satisfactory for 1^-yr-old Merino rams used in paddock mating. The difference in fertility found between the young exotic and the mature naturalized groups of rams was unexpected in view of the general similarity of the behavioural observations between the groups.…”
Section: Discussionmentioning
confidence: 93%